A Report on the C-E Translation of Running Like Wind (Excerpts) Based on Reception Aesthetics (Journal of Global Humanities and Social Sciences, 2023)
This is a report on Chinese-English translation. The source text is selected from the children’s literature Running Like Wind by Deng Xiangzi, a Hunan children’s literature writer. There is no English translation of this book yet. The book tells the life experience of the fifth-grade girl Juduo in her grandmother’s hometown, Hongfengping. It depicts Juduo’s kindness and diligency, guiding children to find the truth of life. Under the guidance of Reception Aesthetics, this translator fully considers children’s mind, thought and reception level. The translation keeps the subjectivity of target readers, meeting their horizon of expectation, and balancing the indeterminacy and vacancy of text meaning. The difficulties in the translation are discussed in case analysis from three levels of vocabulary, sentence and rhetoric, which aims to provide certain reference for the translation of similar children’s literature.